Análisis de la experiencia del Grupo de Teatro Inclusivo Rompecabezas desde las voces de sus protagonistas - González Rojas, Viviana; Sandoval Poveda, Alicia (Universidad de Costa Rica, 2021)
This article relates the replication of Loyd's experience with the Rompecabezas Inclusive Theater Group, with the objective of investigating the satisfaction, appreciation, memories and learnings of the participants in the project. The Rompecabezas Group is part of a project of the Universidad Estatal a Distancia, which is developed in San José, Costa Rica. It's from this project that rises the experience described in this article, from a qualitative approach and an exploratory-descriptive scope. At the end of 2018, a multimodal interview was applied to 18 participants of the group with an age range between 13 and 27 years old, with Autism Spectrum Disorder, Down Syndrome and other disability situations. The results show a generalized liking of the participants for the theater and the various activities related to the project. The opinions of the participants in relation to the benefits that the theater brought them were focused on working with friends, collective triumph and fun. It was possible to determine that they remember and recognize, sometimes with support, the main spaces of the theater workshop activities. The methodology applied to recover the points of view of all the participants proved to be accessible to all their communicative styles. It was possible to highlight the aspects that were intended to be evaluated in this experience in relation to the degree of satisfaction, memories, appreciation and learnings of the people participating in the project.